Advancing Natural Killer Cell Therapy: Genetic Engineering Strategies for Enhanced Cancer Immunotherapy - Park, Joo Dong; Shin, Ha Eun; An, Yeon Su; Jang, Hye Jung; Park, Juwon; Kim, Se-Na; Park, Chun Gwon; Park, Wooram (대한진단검사의학회, 2025)
Natural killer (NK) cells are pivotal innate immune system components that exhibit spontaneous cytolytic activity against abnormal cells, such as infected and tumor cells. NK cells have shown significant promise in adoptive cell therapy because of their favorable safety profiles and minimal toxicity in clinical settings. Despite their advantages, the therapeutic application of unmodified NK cells faces challenges, including limited in vivo persistence, particularly in the immunosuppressive tumor microenvironment. Recent advances in genetic engineering have enhanced the therapeutic potential of NK cells by addressing these limitations and improving their therapeutic efficacy. In this review, we have described various methodologies for the genetic modification of NK cells, including viral vectors, electroporation, and nanoparticle-based approaches. The ongoing research on nanomaterialbased approaches highlights their potential to overcome current limitations in NK cell therapy, paving the way for advanced cancer therapy and improved clinical outcomes. In this review, we also emphasize the potential of engineered NK cells in cancer immunotherapy and other clinical applications, highlighting the expanding scope of NK cell-based treatments and the critical role of innovative genetic engineering techniques.